The Correlation of Learning Motivation with Critical Thinking Skills for Accounting Learning - Lisya Nurlaily Hajar Marfuah; Sunardi Sunardi; Susilaningsih Susilaningsih (Budapest International Research and Critics University, 2022)
The research objective was to examine the correlation between learning motivation and critical thinking skills. This research design was descriptive correlation research with a quantitative approach. Additionally, the research sample consisted of 72 students. The data collection technique used learning motivation questionnaires and a critical thinking ability test. The data were analyzed using Pearson product-moment correlation analysis and a simple regression test assisted by IBM SPSS 20. The results of the correlation test obtained rxy = 0.367. Therefore, it can be interpreted that the correlation category was at a low correlation level. Furthermore, using a simple linear regression test, the researchers got an R-square value = 0.135. It meant that learning motivation contributed 13.5% to critical thinking skills, with a significance through tcount (3,300) > ttable (1,994). The results showed that there was a significant correlation between critical thinking skills with learning motivation.